Evaluasi dan Optimasi Penjadwalan Menggunakan Metode PDM dan Crashing untuk Mempercepat Durasi Pengerjaan Proyek (Studi Kasus Proyek Steel Structure - Primary Crushing) - Muhammad Febri Ariyanto; Renanda Nia Rachmadita; Aditya Maharani (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
Project is a production process that is unique, and is carried out within a certain period of time with limited resources to achieve the targets set. Steel Structure - Primary Crushing is one of mining company’s projects in East Java and is carried out by PT. Lintech Duta Pratama. But this project is past the specified deadline These lateness have consequences like fines or decreased client’s trust toward company’s performance and affect completion for other projects. Optimization is needed to avoid delays. The scheduling method used is a Precedence Diagram Method (PDM) that simpler for overlapping activities. To get a shorter duration of project completion, acceleration (crashing) analysis must be done. The results of the study obtained the duration of acceleration from 143 days to 125 days. The acceleration has two alternative, with overwork that increased the costs by 8,97% from the normal costs. While the other alternative is to add more worker that increased the costs by 0,65%. The cost of increasing the worker is lower so that alternative has the optimal cost and time.